Prize money earnings of tennis professionals and the impact of COVID-19 pandemic - Vladimir Šimić (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2021)
Purpose: The purpose of this study is to investigate the effects of COVID-19 pandemic on the earnings of tennis professionals. With the COVID-19 pandemic being an unmatched blow to the global economy resulting in one of the largest global recessions in recorded history, it might be expected that some sectors will be hit harder than others. Tennis world was particularly strongly hit, practically stopping for five long months. The corona year provides a unique occasion to revisit the issue of the earnings of top tennis professionals and make comparisons with the normal tennis years. The opportunity to collect the fresh data makes these comparisons interesting and timely. Design/methodology/approach: Using the most recent data we constructed the database on the prize money earnings of the TOP 100 tennis professionals. This allowed an investigation of the earnings of tennis professionals in general, but of particular interest in this paper was the impact of the COVID-19 pandemic on these earnings. The data collected for the pandemic year (2020) enabled a comparison with the normal years (2019 and 2018) revealing some interesting findings. The source of the data for investigation conducted in this study is the ATP (Association of Tennis Professionals) website. Findings: The empirical investigation conducted in this paper finds a strong negative impact of the COVID-19 pandemic on the tennis world and prize earnings of the top tennis professionals. The analysis also suggests that a decline in inequality among the top tennis professionals might be another consequence of the pandemic. Research limitations/implications: While the empirical investigation on the impact of the COVID-19 on the tennis world conducted in this paper provides some interesting insights, it also opens a couple of avenues for future research. It might be interesting to conduct a comprehensive study of the earnings of all tennis professionals, not just those belonging to the TOP 100 group. In addition, the associated dynamics may be interesting to explore on the women's tour and make comparisons on the differences of the effects of the pandemic across the ATP and WTA tours. Data limitations might be seen as a serious obstacle for these investigations, but the analysis in this paper provides a direction as to how these obstacles might be circumvented possibly resulting in more interesting studies to come. Originality/value: Many studies have investigated the economic effects of the COVID-19 pandemic. With its focus on the tennis world the present study makes a contribution to the empirical literature by filling the gap on the effects of the pandemic on the sports industry. The study also opens interesting avenues for future research, especially on the impact of the pandemic on inequality.
Keywords: J24; J33; Z21; 330; COVID-19 pandemic; ATPplayers; earnings